Recognition of Community Environment: Character Education-Based Student Program: Looking at the Implementation of the PLM Program at SMAIT Al Irsyad Purwokerto - Anhar, Rofik (International Conference of Moslem Society, 2019)
Education is a big investment for all people, especially for parents. It is important for parents to decide the best educational institutions for their children. They will ask their relatives, neighbors, or even internet. It is almost confirmed that the decisions the parents take for determining a certain school will bring out great expectations for their children, such as being excellent, religious, intelligent, having live skills and many more. Such great expectations above are indeed supposed to be parents’ visions, educators and even country. In the formulation of the Law on the National Education System states that the aims of the National Education are at developing learners’ potentials so that they become persons imbued with human values who are faithful and pious to one and only God; who possess morals and noble character; who are healthy, knowledgeable, competent, creative, independent; and as citizens, are democratic and responsible. The idealism of the National Education’s aims seems to be a Utopia after arising certain phenomena, like several teenagers who is still in student age involve promiscuity, drug abuse, pornography, gadget addiction and loss of respect for parents. Moreover, many cases of prosecutions to parents because the demand that is not granted. School that as one of the pillars of educations, besides family and society has the strategic position for resolving the such problems. The requirements of curriculum management, human resources, and characters building-based students’ programs urge to be carefully formulated and can be implemented. The paper describes the students’ program in the form of the introduction of society environment (PLM) that is held by Al Irsyad Islamic Senior High School of Purwokerto. While there is a program called Community Service Program (KKN) in higher education, it is likewise the program in this school named Introduction of Society Environment (PLM). The program is attractive because it contains many values related to the characters building reinforcements. At least there are nine characters that can be built through this program, such as religious, tolerance, discipline, hard work, nationalism, loving country, being communicative, social and community care. The activities that carried out in the program are the repair of house and mosque, the clothes and staple foods distribution, the SMAIT teaching, the great recitation and free medical treatment. Keywords: education, students’ program, and characters building